2009
DOI: 10.1007/s11274-009-0029-z
|View full text |Cite
|
Sign up to set email alerts
|

Production of lactic acid from date juice extract with free cells of single and mixed cultures of Lactobacillus casei and Lactococcus lactis

Abstract: The production of lactic acid from date juice by single and mixed cultures of Lactobacillus casei and Lactococcus lactis was investigated. In the present conditions, the highest concentration of lactic acid (60.3 g l -1 ) was obtained in the mixed culture system while in single culture fermentations of Lactobacillus casei or Lactococcus lactis, the maximum concentration of lactic acid was 53 and 46 g l -1 , respectively. In the case of single Lactobacillus casei or Lactococcus lactis, the total percentage of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 19 publications
3
25
0
1
Order By: Relevance
“…This showed that, the presence of glucose exerted a partial inhibition on fructose utilization. Nancib et al (2009) observed a similar trend in LA production from date juice extract by L. casei and Lactococcus lactis. Both bacteria utilized glucose more rapidly than fructose in the early stage of the cultures.…”
Section: Lactic Acid Production From Glucose and Fructosesupporting
confidence: 66%
See 1 more Smart Citation
“…This showed that, the presence of glucose exerted a partial inhibition on fructose utilization. Nancib et al (2009) observed a similar trend in LA production from date juice extract by L. casei and Lactococcus lactis. Both bacteria utilized glucose more rapidly than fructose in the early stage of the cultures.…”
Section: Lactic Acid Production From Glucose and Fructosesupporting
confidence: 66%
“…L. casei was reported to utilize date juice containing glucose (50-55 g/L) and fructose (40 g/L), and produced over 53 g/L LA in 19 h (Nancib et al, 2009). It also could produce LA at a rate of 2.2 g/(Lh) from reconstituted whey powder with a lactose concentration of 103 g/L (Buyukkileci and Harsa, 2004).…”
Section: Lactic Acid Production From White Grape Pomace Extractmentioning
confidence: 99%
“…The lactic-acid production value obtained is lower than most values that have been reported in the literature. For example, Shi et al 40 used immobilized Lactococcus lactis to obtain 142g/L lactic acid from Artichoke; Nancib et al 41 reported 60.3 g/L lactic-acid concentration from date juice using a mixed culture of Lactobacillus casei and Lactococcus lactis. Other research results that have been reported include lactic-acid production using different strains like L. pentosus with lactic acid production of 9g/L with a yield of 0.90g/g from wheat-straw hemicellulose hydrolysates and 10g/L with a yield of 0.61g/g using L. brevis; 42 Bacillus coagulans MXL-9 with lactic acid production of 33g/L and a yield of 0.73g/g from wood hemicellulose extracts (16); Bustos et al 43 reported 46.0g/L lactic-acid concentration and yield of 0.78g/g from vine-trimming hydrolysate using a L. pentosus strain; Buendo et al 18 reported 43.66g/L lactic-acid concentration with a yield of 0.72g/g from wood extract hydrolysate.…”
Section: Lactic Acid Production From Sawdust Hydrolysatementioning
confidence: 99%
“…The fermentative process has a high selectivity towards lactic acid, but the concentration of lactic acid at the end of the fermentation can be considered low (approximately 50 g/L). Only a few strains of lactic bacteria provides high concentrations of lactic acid (approximately 100 g/L) (Budhavaram and Fan, 2009;Gullon et al, 2008;Marques et al, 2008;Nancib et al, 2009).…”
Section: Introductionmentioning
confidence: 99%